Review of the Effects of Diabetes Mellitus Group Education with Practitioner-directed Insulin Dosage Adjustments on Glycaemic Control at a Public Sector Primary Health Care Clinic in Khayelitsha - Neumuller, Caroline (Department of Public Health and Family Medicine, 2024)
Aim: In view of the high burden of poorly controlled diabetes mellitus in South Africa, this study evaluated the effect of diabetes group education sessions, coupled with the provision of practitioner-directed insulin dosage adjustments based on home blood glucose readings, on patients' glycaemic control in the short and medium term. Methods: Using routine data, glycaemic control was assessed before, after and three years after the intervention. Additionally, patients' change in glycaemic control over a three-year period was compared to a control group. Results: After the group education sessions and insulin dosage adjustments, the mean HbA1c of 66 intervention patients decreased by 2.03% in the short term, from 12.57% (95%CI [12.05%, 13.09%]) to 10.54% (95%CI [9.96%, 11.11%]), and by a further 0.43% three years after the intervention. However, this change in glycaemic control after three years was not different to that of the control group. Conclusion: The 2% improvement in HbA1c in the short term is a significant achievement; although this is related to patients' poor initial glycaemic control. The control group's similar improvements over a three-year period is due to the improved clinical care and access to glucose monitors for all patients over the course of the study period at the study facility.